An ecopoetics of agency : writing with the nonhuman in modernist and contemporary poetry / Sarah Bouttier. - Bouttier, Sarah (Environmental cultures series., 2026)
Focusing on a category of poems from the Modernist and contemporary periods which give agency to nonhuman beings and texts themselves, Sarah Bouttier puts form, often neglected within ecocriticism, at the center of the definition of ecopoetics. Grounding ecopoetics in posthumanist ontologies (new materialism, flat ontology and Latour's work on agency), Bouttier explores how the poems collapse the human/nonhuman divide and re-instil wonder at the nonhuman world. By juxtaposing readings of Modernist poets such as D. H. Lawrence, Wallace Stevens and Marianne Moore with contemporary poets such as Les Murray, Pattiann Rogers, Alice Oswald and Kathleen Jamie, the book provides fresh insight into well-known works and offers a new perspective on contemporary ecopoetry.